(untitled) (Research, Society and Development, 2021)
For the implementation of agroforestry systems in the Caatinga and projects for the recovery of degraded areas to be successful practices, the allelopathic effects that will be involved in the system must be considered, as they determine the floristic composition and the predominance of plant species. This qualitative narrative review was carried out to obtain better knowledge about the allelopathy of the Caatinga species. It was considered: (a) Factors that influence the allelopathic effect: chemical constituents; pH and osmotic potential; extraction solvent; vegetable organ; physical preparation of plant parts; extract extraction temperature; synergism; extract concentration; evaluation of the allelopathic effect; (b) Factors that influence the quantity and quality of secondary metabolites: domestication of the plant species; physical and physiological characteristics of the seeds of the target species; time of the year; collection time; stress and collection site; interactions between the plant and the microorganisms present in the soil; allelopathic substances (inhibition or stimulus?). Among the possibilities of investigations, the development of studies of allelopathic processes with native tree species stands out with the objective of determining which species are synergistic with each other, with the capacity to favor the success in the recovery of degraded areas and in sustainable management. Find out in what ways the stress conditions (water, salt, thermal, light and nutritional) affect the quantity and quality of secondary metabolites. Research can simulate the effect of the litter of different species of the Caatinga on the germination and development of other species to be used in reforestation programs and in agrosilvipastoral systems.